Technology Integration in Syrian Medical Education From the Perspective of Students and Faculty: A Cross-Sectional Evaluation - Subhiya Hassoun; Mayssoon Dashash; Adnan Baddour (JMIR Formative Research)
Abstract BackgroundTechnology-enhanced learning (TEL) has become increasingly vital in global medical education, offering significant advantages in knowledge acquisition, communication, motivation, and student engagement. In Syria, a country facing prolonged crises, there is an urgent need to evaluate the integration of technology within medical education to address institutional limitations and support student learning. ObjectiveThe aim of this study is to evaluate the awareness, perceived challenges, and needs regarding the integration of technology in medical education from the perspectives of students and faculty at Syrian medical colleges. MethodsA cross-sectional survey was conducted during the 2023‐2024 academic year across Syrian universities. Stratified random sampling was used to recruit 500 medical students and 200 faculty members. Two tailored, self-administered questionnaires were used, covering motivation, perceived benefits, challenges, and suggestions for technology integration. Validity was assessed through expert review and pilot testing (n=30), and internal consistency was confirmed (Cronbach α=0.6‐0.7). Quantitative data were analyzed using descriptive statistics, t ResultsAmong medical students, 94% (470\500) agreed that integrating technology into medical education is essential, with similar agreement from 93.5% (187\200) of faculty. No significant differences were found in student responses based on specialization (PPP ConclusionsThere is a strong consensus among Syrian medical students and faculty on the value and necessity of integrating technology in medical education. Despite infrastructure and administrative challenges, both groups recognize TEL as a powerful tool for improving clinical competencies, student motivation, and academic engagement. Institutional commitment, curricular reform, and tailored training are essential to achieving sustainable, effective technology integration.